Incorporating expert judgement into life insurance and life Takaful Companies’ efficiency measurement through DEA-AR/FAHP approach / Nur Azlina Abd Aziz … [et al.] - Abd Aziz, Nur Azlina; Mahad, Nor Faradilah; Mohd Mahyideen, Jamilah; Kasim, Eley Suzana (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Increased competition within the insurance industry has led to the critical need for insurance companies to utilise their resources efficiently. Data Envelopment Analysis (DEA) model has been widely used to measure the relative efficiency of these companies. However, a limitation of the conventional model indicates that certain crucial factors were ignored in the analysis resulting in unrealistic efficiency outcomes. Hence, the present study aims to provide a more robust efficiency measurement by incorporating the subjective value of judgement in the standard DEA through a hybrid model which integrates Constant Return Scale (CRS) model of DEA, Assurance Region Type I (ARI), and Fuzzy Analytic Hierarchy Process (FAHP) method. This proposed DEA-AR/FAHP model was applied on the data gathered from 22 Malaysian life insurance and Takaful companies between 2017 and 2018. Findings revealed that the model provides an improved efficiency assessment through the elimination of zero weights and hence deliver more realistic results.